An Ottoman Mentality : The World of Evliya Çelebi (revised second edition) - Dankoff, Robert (The Ottoman Empire and its Heritage, 2006)
In his huge travel account, Evliya Çelebi provides materials for getting at Ottoman perceptions of the world, not only in areas like geography, topography, administration, urban institutions, and social and economic systems, but also in such domains as religion, folklore, sexual relations, dream interpretation, and conceptions of the self. In six chapters the author examines: Evliya's treatment of Istanbul and Cairo as the two capital cities of the Ottoman world; his geographical horizons and notions of tolerance; his attitudes toward government, justice and specific Ottoman institutions; his social status as gentleman, character type as dervish, office as caller-to-prayer and avocation as traveller; his use of various narrative styles; and his relation with his audience in the two registers of persuasion and amusement. An Afterword situates Evliya in relation to other intellectual trends in the Ottoman world of the seventeenth century.